Efficacy and safety of anlotinib in patients with unresectable or metastatic bone sarcoma: A retrospective multiple institution study. (26th September 2021) - Liu, Zhiyong; Gao, Songtao; Zhu, Liangyu; Wang, Jiaqiang; Zhang, Peng; Li, Po; Zhang, Fan; Yao, Weitao
Abstract: Background: Tyrosine kinase inhibitors (TKIs) such as cabozantinib, regorafenib have demonstrated encouraging activity in prolonging progression‐free survival (PFS) in several bone sarcoma entities in prospective clinical trials. This retrospective study aims to analyze the safety and efficacy of anlotinib, a novel multi‐target TKI, in patients with locally unresectable or metastatic bone sarcoma at three institutions. Methods: Patients with advanced bone sarcoma administered anlotinib 12 mg once daily, 2 weeks on/1 week off, from June 2018 to June 2020, until disease progression or intolerance of treatment. The primary endpoints were objective response rate (ORR) and PFS. Results: Forty‐eight patients were analyzed: 27 have osteosarcoma, 9 have chondrosarcoma, 8 have Ewing's sarcoma, and 3 have chordoma. The median age was 24 years (range, 16–68 years), and the median number of prior regimens was 1 (range, 0–4). Until the final follow‐up, five patients obtained a partial response and while 24 achieved stable disease. The ORR in all patients was 10.4%, and the median PFS was 4.6 months, with a progression‐free rate (PFR) at 3 months and 6 months of 72.9% and 35.4%, respectively. The ORR and median PFS varied much among tumor subtypes. The most frequent grade 3–4 adverse events (AEs) were pneumothorax, hand‐foot syndrome, cholesterol elevation, hypertriglyceridemia, and fatigue. No patients died from anlotinib‐related AEs during the study period. Conclusions: Anlotinib may show promising antitumor activity in unresectable or metastatic bone sarcoma. The ORR and median PFS of anlotnib are similar to those of other targeted drugs in different subtypes of sarcomas. The AEs were generally mild and tolerated well. Further studies of anlotinib in selected subtypes of bone sarcoma are needed. Abstract : Anlotinib may show promising antitumor activity in unresectable or metastatic bone sarcoma. The ORR and median PFS of anlotnib were similar to those of other targeted drugs in different subtypes of sarcomas. The AEs were generally mild and well tolerated. Further studies of anlotinib in selected subtypes of bone sarcoma are needed.